A study of applause in family ritual. (June 2022) - Remisiewicz, Łukasz; Rancew-Sikora, Dorota
With reference to the previous empirical works on applause, we explore the roles it plays during the first birthday celebration using multimodal analysis. Particularly, we focus on modes of its initiation and collaborative enactment. The empirical material includes 25 videos from different Polish families. The analysis demonstrates that applause works in interaction (1) as a ritual anchor that allows the participants to move to either the end or the next sequence of the ritual, (2) as an appreciative assessment of the previous action, (3) as a device for focusing joint attention, which coordinates the interaction of participants and (re)focuses the attention on the most important actor/recipient of the ritual.